Peramalan Produksi Kelapa Sawit di Provinsi Jambi dengan Menggunakan Pendekatan Model Box-Jenkins - Sepitria Mardianti; Zulgani Zulgani; Yohannes Vyn Amzar (Journal of Islamic Banking, 2025)
Palm oil is one of the leading commodities in the plantation sector in Indonesia which plays a strategic role in driving national economic growth, rural development, and poverty alleviation. Indonesia has been a major producer of palm oil in the world since 2006, with Jambi Province as one of the largest producing regions. This study aims to analyze 1) how palm oil production develops in Jambi Province, 2) which ARIMA model is the most appropriate and accurate for forecasting palm oil production in Jambi Province for the next 5 years, 3) how the results of forecasting the amount of palm oil production in Jambi Province using the most effective model. The data used in this study is the annual time series data of palm oil production in Jambi Province for the period 1989 to 2023 sourced from the Central Statistics Agency of Jambi Province and the Plantation Office of Jambi Province. The results of this study indicate that the best Box-Jenkins model for forecasting palm oil production in Jambi Province is ARIMA (2,1,1) with an Akaike Information Criterion (AIC) value of 27.26197 and a Schwarz Information Criterion (SIC) of 27.48643 and a Hannan-Quinn Criterion (HC) of 27.33851, which states that the value of palm oil production has increased from 2024 to 2028 with an average growth in palm oil production during the forecasting period estimated at around 2.8% per year.